Reception of Perempuan Berkalung Sorban Movie among Islamic Senior High School Students - Febriyanto Ngabito; Sayama Malabar; Karmin Baruadi (TRANSBAHASA, 2021)
This study aims to describe the responses and reception of Perempuan Berkalung Sorban movie among Islamic senior high school students’ and its implementation in Indonesian language learning. This qualitative descriptive study employs a reception approach. Interviews, questionnaires, and documentation techniques have been performed in collecting the data. The data analysis techniques consist of several procedures, (1) identifying data from parts of the movie that elicit students’ response in the form of mimics or expressions as well as oral and written responses; (2) classifying response and reception data; (3) interpreting and describing the results of the analysis; and (4) concluding the results of the analysis. The results reveal that (1) the students’ positive response is shown by happy expression, while negative responses consist of sad, annoyed, angry, scared, shocked, disgusted, disappointed, and concerned expressions; (2) The students' verbal and written receptions to the movie are shown with positive explanations as the movie exuded the values for guide of life, and the negative ones are shown due to the treatment that marginalized women; (3) the implementation of the results on Indonesian language learning is carried out by designing a learning development. The design is based on a reception approach on the basic competencies of understanding thecontents of literary works (movie) for the second semester of twelve grade students in Islamic senior high school.